Pelatihan gender budgeting atau anggaran responsif gender di Dinas Sosial Pemberdayaan Perempuan dan Perlindungan Anak (Dinsos P3A) Kabupaten Rokan Hulu - Rahmita Budiartiningsih; Hendro Ekwarso; yelly Zamaya; Bunga Chintia Utami (Unri Conference Series: Community Engagement, 2022)
The policy on gender mainstreaming began with the issuance of Presidential Instruction No. 9/2000. The follow-up to this regulation was the issuance of circular letter No. 270/M.PPN/11/2012; number : SE-33/MK.02/2012; number : 050/4379A/SJ and SE46/MPP-PA/11/2012 concerning the National Strategy for the Acceleration of Gender Mainstreaming (PUG) through Gender Responsive Planning and Budgeting (PPRG). The seven pre-requisites of PUG, namely commitments, policies, institutions, resources, analytical tools, disaggregated data, and public support, have not been fully met by Ministries/Agencies and local governments. Gender integration in planning, budgeting, implementation, monitoring, and evaluation of development policies, programs and activities at the central and regional levels still needs to be strengthened. Referring to this, this service activity is carried out to strengthen institutions in the government in the Rokan Hulu Regency area in gender mainstreaming. The activity partner in this service activity is the Social Service for Women's Empowerment and Child Protection (Dinsos P3A) of Rokan Hulu Regency as the center of government in implementing policies on women and related agencies in the implementation of planning, budgeting and evaluating gender-responsive local government programs